Feeling sorry for Celia - Moriarty, Jaclyn (New York : St. Martin's Press, 2001)
An epistolary novel about a teenager named Elizabeth, made up of notes and letters from her best friend, a runaway named Celia; Christina, the new pen pal Elizabeth reluctantly takes on for a school assignment; her busy mother; and Elizabeth's own angst-ridden mind.
Library Journal.
Notable/Best Books (A.L.A.).
School Library Journal.
Young Adult
Keywords: Teenage girls -- Fiction; Bildungsromans; Epistolary fiction; Teenagers -- Fiction; Australia -- Fiction; Australia -- Fiction; Bildungsromane; Epistolary fiction